The Iltmo. Trejo y Sanabria and the educational centers of Tucumán.: Foundation of the University of Cordoba - Liqueno, José María (Universidad Nacional de Córdoba, 1916)
Education and its social significance. -The need for educational centers in the Colony. -Efforts of the priesthood to establish them. -The Province of Tucumán and the Illustrious Trejo. -State of the education. -Treja and the educational establishments. -Foundation of moral sciences. -The Convictory of St. Francis Xavier in Cordoba. -Character and mission of the Convictory. -Its duration. -Fulfilled aspirations of Trejo. -Founding of the University of Cordoba. -Writing. -Main articles of the same. -Opening of university studies. -Letter from the bishop to S. M. -Academic degrees. Observations that are resolved. -Reception to the prelate by the students of Cordoba. -Trejo's work to increase his income. -Testament of Iltmo. Treja. -Synthesis of the same. -Conclusion and summary.